2022
DOI: 10.1093/ehjopen/oeac059
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular assessment with artificial intelligence increases the diagnostic accuracy of stress echocardiography

Abstract: Aims To evaluate whether left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS), automatically calculated by artificial intelligence (AI), increases the diagnostic performance of stress echocardiography (SE) for coronary artery disease (CAD) detection. Methods and Results SEs from 512 participants who underwent a clinically-indicated SE (with or without contrast) for the evaluation of CAD from 7 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Although previous studies have examined the accuracy of other ML models for LVEF estimation, they did not utilize clinician driven POCUS and instead focused on echocardiogram data [ 1 , 16 , 17 ] or imaging performed by sonographers [ 14 ]. Asch et al, showed good agreement in an ML model estimation of LVEF compared to reference values on cardiac POCUS.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have examined the accuracy of other ML models for LVEF estimation, they did not utilize clinician driven POCUS and instead focused on echocardiogram data [ 1 , 16 , 17 ] or imaging performed by sonographers [ 14 ]. Asch et al, showed good agreement in an ML model estimation of LVEF compared to reference values on cardiac POCUS.…”
Section: Discussionmentioning
confidence: 99%
“…All LV volumes and LVEF were obtained by performing endocardial tracings and using the biplane method of disks (modified Simpson's rule). Only cases with acceptable‐quality LV views were included, which was defined as lack of apical foreshortening with adequate visualization of all segments and delineation of the entire LV endocardial border by the AI from all views as previously described 16,17 . Longitudinal strain was calculated as the average Legrangian strain from the A4C, A3C, and A2C views.…”
Section: Methodsmentioning
confidence: 99%
“…Only cases with acceptable-quality LV views were included, which was defined as lack of apical foreshortening with adequate visualization of all segments and delineation of the entire LV endocardial border by the AI from all views as previously described. 16,17 Longitudinal strain was calculated as the average Legrangian strain from the A4C, A3C, and A2C views. Cut-offs for mild, moderately, and severely reduced LVEF were determined by the 2015 American Society of Echocardiography (ASE)/European Association of Cardiovascular Imaging (EACVI) guidelines for cardiac chamber quantification.…”
Section: Transthoracic Image Analysismentioning
confidence: 99%
“…In this setting, the Artificial Intelligence-calculated Left Ventricular Ejection Fraction and Global Longitudinal strain (GLS) are demonstrated to provide incremental sensitivity to detect CAD [ 16 ]. Artificial intelligence analysis pipelines efficiently delineate the endocardial surface without requiring advanced training for strain analysis.…”
Section: The Role Of Echocardiographymentioning
confidence: 99%